COMMUNITY SERVICE ON FINANCIAL PARENTING STRATEGIES FOR RESIDENTS OF BOGEM HAMLET, KEBOBAGUNG, SUKODONO, SIDOARJO - Anik Kirana; Fatkul Anam; Fransisca Dwi Harjanti (Bajang Institute, 2025)
Parenting plays a crucial role in shaping children’s ability to live independently and responsibly in the future. To achieve this, parents need to acquire appropriate parenting competencies that support healthy character development. Children’s character is strongly influenced by the parenting styles applied at home, and inappropriate parenting practices may lead to both immediate and long-term negative consequences. Therefore, it is essential for parents to develop adequate parenting knowledge and skills. Importantly, parenting education is not only relevant for families with children but is also valuable for prospective parents as a form of early preparation. The cultivation of positive values—such as religious principles, responsibility, empathy, ethical behavior, diligence, and financial literacy—serves as a fundamental starting point in effective parenting. To ensure clarity and accessibility of the information delivered, this community service activity employs various educational approaches, including lectures, discussions, best practice sharing, and question-and-answer session.